COMPARISON OF ORTHODONTIC TREATMENT RESULTS WITH INVISALIGN AND FIXED APPLIANCE USING PEER ASSESSMENT RATING INDEX - Pakpahan, Evie Lamtiur (Universitas prof. Dr. Moestopo (Beragama), 2023)
Malocclusion is defined as a condition that deviates from normal occlusion. Crowding is the most common malocclusion. Orthodontic treatment is a field of dentistry that plays an essential role in improving facial esthetics, function and stability of good treatment results. Orthodontic treatment offers several methods, such as conventional fixed orthodontic appliances and invisalign. The PAR index is an instrument used to measure deviations from ideal occlusion and to evaluate the results of orthodontic treatment quantitatively by comparing pre-and post-treatment dental models. Purpose: This study aims to compare the efficacy of orthodontic treatment results with invisalign and conventional fixed orthodontic appliances using the PAR Index. Methods: Analyzing databases such as Google Scholar, textbook, Elsevier, PubMed, and various national and international journal websites related to the title of this literature. The references have been selected based on relevant analysis and published in the last ten years, specifically from 2011 to 2021. Results: Based on the PAR index score, there were no significant differences in the efficacy of orthodontic treatment results with invisalign and conventional fixed orthodontic appliances. Conclusion: Both Invisalign and fixed appliances were able to improve the malocclusion. However, Invisalign may not be as effective as fixed appliances